Knowledge Services: A Strategic Framework for the 21st Century Organization - Guy St. Clair (De Gruyter, 2017)
Knowledge Services converges information management, knowledge management (KM), and strategic learning into a single enterprise-wide discipline for the benefit of the business or organization in which it is practiced. With the success of knowledge services as a management methodology, the practice has become an acknowledged framework for strategic knowledge management applicable to all businesses and organizations.
Keywords: 020; Information Science; LIS